2009
DOI: 10.1002/hep.23240
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness identifies two different patterns of fibrosis progression in patients with hepatitis C virus recurrence after liver transplantation

Abstract: Significant liver fibrosis (F > 2) and portal hypertension (hepatic venous pressure gradient[HVPG] > 6 mmHg) at 1 year after liver transplantation (LT) identify patients with severe hepatitis C recurrence. We evaluated whether repeated liver stiffness measurements (LSM) following LT can discriminate between slow and rapid "fibrosers" (fibrosis stage F2-F4 at 1 year after LT). Eighty-four patients who had undergone LT and who were infected with hepatitis C virus (HCV) and 19 LT controls who were not infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 40 publications
4
87
0
2
Order By: Relevance
“…However, liver stiffness measurement (LSM) cannot yet confidently predict the presence of esophageal varices in clinical practice and thus avoid the need for upper GI endoscopic screening of cirrhotic patients [85]. TE could be also valuable for assessing the severity of recurrent hepatitis C after liver transplantation, reducing the need for follow-up liver biopsies [78,[86][87][88][89][90]. It has been recently suggested that TE may perform better for significant fibrosis than serum (direct and indirect) biomarkers [91].…”
Section: Monitoring Of Disease Progressionmentioning
confidence: 99%
“…However, liver stiffness measurement (LSM) cannot yet confidently predict the presence of esophageal varices in clinical practice and thus avoid the need for upper GI endoscopic screening of cirrhotic patients [85]. TE could be also valuable for assessing the severity of recurrent hepatitis C after liver transplantation, reducing the need for follow-up liver biopsies [78,[86][87][88][89][90]. It has been recently suggested that TE may perform better for significant fibrosis than serum (direct and indirect) biomarkers [91].…”
Section: Monitoring Of Disease Progressionmentioning
confidence: 99%
“…Similarly, LSM has proven to be useful to assess histological progression after transplantation (13,14). However, to date, no study has evaluated the association between liver stiffness and clinical events, including graft and patient survival, in recurrent hepatitis C following LT. Only a score comprising three direct serum biomarkers proved helpful to predict the development of clinical decompensations and graft loss in this setting (15), though these markers have not been validated so far.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence that FS accurately predicted non-HCV-related graft damage suggests an extended application of FS in the management of non-HCV-infected LT patients to help decision making for LB. The usefulness of LS in the management of LT patients has been recently confirmed by longitudinal data provided by Carrión et al [47].…”
Section: Non-hcv-infected Liver Transplant Patientsmentioning
confidence: 78%